Utilization of Cow's Rumen Bokashi Enriched with Chicken Manure on Chlorella sp. Cell Density - Fraja Mukti; Rosyadi; Agusnimar; Khairul Hadi; Kurnia Zulfahmi; Nagaraj, Subramani (Department of Aquaculture, 2024)
One of the organic fertilizers that has the potential to cultivate Chlorella sp. is the cow's rumen. To increase the nutrient content in the cow's rumen, the cow's rumen must be made into bokashi and enriched with chicken manure. This study aimed to determine the use of cow's rumen bokashi enriched with chicken manure at different doses on Chlorella sp cell density. The research design used was a Completely Randomized Design (CRD) with 5 treatments and 3 replications, namely P0 (2 g/L cow's rumen bokashi), P1 = 2 g/L cow's rumen bokashi enriched with 2.5 g/L chicken manure, P2 = 2 g/L cow's rumen bokashi enriched with 3.0 g/L chicken manure, P3 = 2 g/L cow's rumen bokashi enriched with 3.5 g/L chicken manure, and P4 = 2 g/L cow's rumen bokashi enriched with 4.0 g/L chicken manure. The results showed that the highest cell density of Chlorella sp. occurred in treatment P3 (i.e. 456.1 ± 15.1 í— 104 cells/mL) and the highest specific growth rate occurred in treatment P0 (i.e. 0.20 ± 0.0/day). Nutrient levels in the culture medium are optimal for Chlorella sp., with nitrate ranging from 0.1375 to 0.2833 mg/L and phosphate ranging from 2.4889 to 2.8650 mg/L. From the results of this study, it can be concluded that the use of cow's rumen bokashi enriched with chicken manure had a very significant effect on cell density and specific growth rate of Chlorella sp. (P<0.01).